Surveillance report for active trachoma, 2006: National Trachoma Surveillance and Reporting Unit - Tellis, Betty; Keeffe, Jill E; Taylor, Hugh R (Communicable Diseases Intelligence, 2007)
The National Trachoma Surveillance and Reporting Unit (NTSRU) was established in November 2006 to improve the quality and consistency of data collection and reporting of active trachoma in Australia. Active trachoma data collected in 2006, prior to the commencement of the NTSRU, were reported by the Northern Territory, South Australia and Western Australia. In most regions, Aboriginal children aged 5–9 years were screened for signs of active trachoma, following the World Health Organization simplified trachoma grading system. In the Northern Territory the Healthy School Aged Kids program conducted school-based screening for active trachoma in 74 schools in five regions (n= 2,253). In South Australia Aboriginal school children presented for active trachoma screening when an eye team visited five Aboriginal Community Controlled Health Services (n= 275). In Western Australia population health units in collaboration with staff from population health care services, conducted school based screening for active trachoma in 53 schools in four regions (n= 1,719). Regional active trachoma prevalence for 2006 varied between the states and the Northern Territory with reported prevalences ranging from: Northern Territory = 2.5%–30%, South Australia = 0%–25%, and Western Australia = 18%–53%. Few data were reported on facial cleanliness or other aspects of the SAFE strategy, and no data were reported for trichiasis. Commun Dis Intell 2007;31:366–374.